2013
DOI: 10.1038/ismej.2013.163
|View full text |Cite
|
Sign up to set email alerts
|

Microbial expression profiles in the rhizosphere of willows depend on soil contamination

Abstract: The goal of phytoremediation is to use plants to immobilize, extract or degrade organic and inorganic pollutants. In the case of organic contaminants, plants essentially act indirectly through the stimulation of rhizosphere microorganisms. A detailed understanding of the effect plants have on the activities of rhizosphere microorganisms could help optimize phytoremediation systems and enhance their use. In this study, willows were planted in contaminated and non-contaminated soils in a greenhouse, and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(152 citation statements)
references
References 86 publications
8
139
1
1
Order By: Relevance
“…In contrast to these observations, differences in the composition of microbial communities in the rhizosphere of Arabidopsis thaliana are likely to be determined by soil type, rather than a unique selection by plant genotype (Lundberg et al, 2012). Along the same lines, Yergeau et al (2014) demonstrated that soil contamination that leads to shifts in community composition ultimately influences the composition of assembled communities in the rhizosphere of willows. In the phyllosphere, which is a niche less subjected to the high density of organism inoculum from soil, the plant genotype seems to exert a stronger selective influence, as observed in specific microbial communities in the phyllosphere of plants living in mangroves Rigonato et al, 2012).…”
Section: Drivers Of Plant-associated Microbial Communitiesmentioning
confidence: 72%
“…In contrast to these observations, differences in the composition of microbial communities in the rhizosphere of Arabidopsis thaliana are likely to be determined by soil type, rather than a unique selection by plant genotype (Lundberg et al, 2012). Along the same lines, Yergeau et al (2014) demonstrated that soil contamination that leads to shifts in community composition ultimately influences the composition of assembled communities in the rhizosphere of willows. In the phyllosphere, which is a niche less subjected to the high density of organism inoculum from soil, the plant genotype seems to exert a stronger selective influence, as observed in specific microbial communities in the phyllosphere of plants living in mangroves Rigonato et al, 2012).…”
Section: Drivers Of Plant-associated Microbial Communitiesmentioning
confidence: 72%
“…Partial 16S ribosomal (rRNA) gene amplicons were produced using the universal primers F343 (5'-TAC GGR AGG CAG CAG-3') and R534 (5'-ATT ACC GCG GCT GCT GGC-3') as in Yergeau et al (2014). The primers contained 10-bp multiplex identifiers (MIDs) and adaptor sequences for Ion Torrent sequencing (Yergeau et al 2012;Bell et al 2013).…”
Section: Ion Torrent 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…Apart from DGGE, thermal gradient gel electrophoresis, and fluorescence in situ hybridization, clone library construction of microbial community-amplified products and sequencing emerged as other supporting techniques for better understanding of microbial ecology (Muyzer, 1999). Furthermore, there are many newer techniques used to understand the microbiome, from metagenomics to metaproteomics (Friedrich, 2006;Mendes et al, 2011;Knief et al, 2012;Rincon-Florez et al, 2013;Schlaeppi et al, 2014;Yergeau et al, 2014). These techniques cover the whole microbiome, instead of selecting particular species, unlike conventional microbial analysis.…”
mentioning
confidence: 99%